2006
DOI: 10.1038/sj.onc.1209849
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the hyaluronan-CD44 interaction by merlin contributes to the tumor-suppressor activity of merlin

Abstract: Mutation or loss of expression of merlin is responsible for neurofibromatosis type 2 (NF2), which is characterized by the development of schwannomas and other tumors of the nervous system. Like the ERM (ezrin-radixin-moesin) proteins, merlin interacts with CD44, a cell-surface receptor for hyaluronan (HA) that promotes tumorigenesis. However, the relationship between merlin and CD44 and the mechanism by which merlin exerts its tumorsuppressor function have not been elucidated. In the present study, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 62 publications
2
76
0
Order By: Relevance
“…Ezrin is the essential molecule that stimulates proliferation and migration, whereas merlin is the molecule that inhibits cell proliferation. Several investigations revealed that the expression and activation of ezrin and merlin can be regulated by HA [16,17]. Therefore, it has been proposed that merlin and ezrin are probably involved in the different regulatory processes in vascular endothelial cells (VECs) associated with glycans and oligosaccharides [18]; however, there is no definitive evidence for this assertion.…”
Section: Introductionmentioning
confidence: 86%
“…Ezrin is the essential molecule that stimulates proliferation and migration, whereas merlin is the molecule that inhibits cell proliferation. Several investigations revealed that the expression and activation of ezrin and merlin can be regulated by HA [16,17]. Therefore, it has been proposed that merlin and ezrin are probably involved in the different regulatory processes in vascular endothelial cells (VECs) associated with glycans and oligosaccharides [18]; however, there is no definitive evidence for this assertion.…”
Section: Introductionmentioning
confidence: 86%
“…Interestingly, Bai et al (2007) recently showed that the first 50 amino acids of merlin contain regulatory residues that affect the interplay between merlin, ezrin, actin and CD44. Phosphorylation of serine 10 could be involved in regulating the formation of these complexes.…”
Section: Pka Phosphorylation Of Merlin M Laulajainen Et Almentioning
confidence: 99%
“…47 Moreover, merlin overexpression inhibits CD44 mediated cell linkage to HA, in turn inhibiting the interaction of CD44 with both ezrin and actin. 48 We thus evaluated also merlin interaction with ezrin and CD44. The experiments showed that merlin co-immunoprecipitated with both ezrin and CD44 (Fig.…”
Section: Ezrin-related Metastatic Functionsmentioning
confidence: 99%